Clinical evaluation and reproducibility of the Pastorex Aspergillus antigen latex agglutination test for diagnosing invasive aspergillosis. Issue 5 (May 1995) - Verweij, P E; Rijs, A J; De Pauw, B E; Horrevorts, A M; Hoogkamp-Korstanje, J A; Meis, J F
Abstract : AIMS--The performance of the Pastorex Aspergillus antigen latex agglutination test for the detection of galactomannan in sera of patients at risk for invasive aspergillosis was evaluated, and the impact of storage on the reproducibility of the antigen titre was tested. METHODS--During a one year period, 392 serum samples were obtained from 46 patients at risk for invasive aspergillosis and tested for the presence of galactomannan using an Aspergillus latex agglutination test (Pastorex). Twenty three positive serum samples which had been stored at -20 degrees C for 2-16 months were retrospectively retested. Furthermore, two positive serum samples were stored at -20 degrees C and -70 degrees C and prospectively tested at three month intervals for a period of 15 months. RESULTS--The Pastorex Aspergillus test was positive in eight patients with microbiological, radiological, or histological evidence for invasive aspergillosis, but was negative in the initial serum sample from five of these patients. In two patients with histological evidence for invasive aspergillosis no positive reaction was found in six samples. Six of 13 (45%) serum samples which had been stored at -20 degrees C for longer than six months had lost reactivity, while one of 10 (10%) samples had lost reactivity when stored up to six months. Two serum samples which had been stored at -20 degrees C and -70 degrees C and prospectively retested at three month intervals for 15 months, maintained stable antigen titres. CONCLUSIONS--The Pastorex Aspergillus test is too insensitive to diagnose invasive aspergillosis in an early stage, but may contribute to the diagnosis when cultures remain negative and serial samples are obtained. To maintain a good reproducibility, serum samples should be stored at -70 degrees C when the period of storage exceeds six months.